Completeness Theorem for Eigenparameter Dependent Dissipative Dirac Operator with General Transfer Conditions - Kun Li; Maozhu Zhang; Jinming Cai; Zhaowen Zheng (Journal of Function Spaces)
This paper deals with a singular (Weyl’s limit circle case) non-self-adjoint (dissipative) Dirac operator with eigenparameter dependent boundary condition and finite general transfer conditions. Using the equivalence between Lax-Phillips scattering matrix and Sz.-Nagy-Foiaş characteristic function, the completeness of the eigenfunctions and associated functions of this dissipative operator is discussed.